2016
DOI: 10.1371/journal.pone.0165815
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Tree Diversity on Different Aspects of Insect Herbivory along a Global Temperature Gradient - A Meta-Analysis

Abstract: Forests with higher tree diversity are often assumed to be more resistant to insect herbivores but whether this effect depends on climatic conditions is so far poorly understood. In particular, a forest’s resistance to herbivory may depend on mean annual temperature (MAT) as a key driver of plant and insect phenology. We carried out a global meta-analysis on regression coefficients between tree diversity and four aspects of insect herbivory, namely herbivore damage, abundance, incidence rate and species richne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 54 publications
(87 reference statements)
3
41
1
Order By: Relevance
“…While many reasons have been proposed to explain discrepancies in the literature, including insect herbivores' host specificity (Castagneyrol, Jactel, Vacher, et al, 2014;Jactel & Brockerhoff, 2007) or climatic conditions (Kambach, Kühn, Castagneyrol, & Bruelheide, 2016), the methodology of herbivory assessment may be another potential explanation. While many reasons have been proposed to explain discrepancies in the literature, including insect herbivores' host specificity (Castagneyrol, Jactel, Vacher, et al, 2014;Jactel & Brockerhoff, 2007) or climatic conditions (Kambach, Kühn, Castagneyrol, & Bruelheide, 2016), the methodology of herbivory assessment may be another potential explanation.…”
Section: Discussionmentioning
confidence: 99%
“…While many reasons have been proposed to explain discrepancies in the literature, including insect herbivores' host specificity (Castagneyrol, Jactel, Vacher, et al, 2014;Jactel & Brockerhoff, 2007) or climatic conditions (Kambach, Kühn, Castagneyrol, & Bruelheide, 2016), the methodology of herbivory assessment may be another potential explanation. While many reasons have been proposed to explain discrepancies in the literature, including insect herbivores' host specificity (Castagneyrol, Jactel, Vacher, et al, 2014;Jactel & Brockerhoff, 2007) or climatic conditions (Kambach, Kühn, Castagneyrol, & Bruelheide, 2016), the methodology of herbivory assessment may be another potential explanation.…”
Section: Discussionmentioning
confidence: 99%
“…predators and parasitoids). Also, while earlier meta‐analyses on plant diversity effects often did not distinguish between herbivore responses in terms of abundance and damage (Castagneyrol, Jactel, Vacher, Brockerhoff, & Koricheva, ; Jactel & Brockerhoff, ), a recent meta‐analysis of tree species diversity effects on herbivores by Kambach, Kühn, Castagneyrol, and Bruelheide () has revealed that herbivore abundance, species richness and damage may be differently affected by plant diversity and it is important to distinguish between these response variables.…”
Section: Introductionmentioning
confidence: 99%
“…We used a tree diversity experiment replicated at two sites in the UK, in which local and climate‐matched oak provenances are planted as monocultures or in mixtures of provenances and species. There is increasing evidence that tree diversity effects on pest organisms are context dependent and can be modulated by abiotic conditions such as temperature and water availability impacting upon plant growth and functional traits (Castagneyrol, Moreira, & Jactel, ; Kambach, Kühn, Castagneyrol, & Bruelheide, ; Walter et al, ). By studying replicate trials between years (2 years of data from one site) and between trials, we looked for consistent impacts of provenance identity and tree diversity across space and time.…”
Section: Introductionmentioning
confidence: 99%
“…However, non-native provenances may also experience stressful growing conditions under current local climates, leading to reduced tree vigor. Plant stress generally has a negative effect on the performance of primary foliar insect herbivores and biotrophic pathogens, while plant vigor can have the opposite effect (Huberty & Denno, 2004;Jactel et al, 2012). Despite the potential importance of introduced provenances as a future-proofing strategy against climate change, few experimental studies exist comparing the growth characteristics and pest resistance of local versus climate-matched provenances under current climatic conditions (Barsoum, 2015;Broadmeadow et al, 2005).…”
mentioning
confidence: 99%